The effects of the cluster environment on the galaxy mass-size relation in MACS J1206.2-0847 - Kuchner, U.; Ziegler, B.; Verdugo, M.; Bamford, S.; Häußler, B. (EDP Sciences, 2017)
The dense environment of galaxy clusters strongly influences the nature of galaxies. Their abundance and diversity is imprinted on the stellar-mass–size plane. Here, we study the cause of the size distribution of a sample of 560 spectroscopic members spanning a wide dynamical range down to 108.5 M (log (M)-2) in the massive CLASH cluster MACSJ1206.2-0847 at z=0.44. We use Subaru SuprimeCam imaging covering the highest-density core out to the infall regions (3 virial radii) to look for cluster-specific effects on a global scale. We also compare our measurements to a compatible large field study in order to span extreme environmental densities. This paper presents the trends we identified for cluster galaxies divided by their colors into star forming and quiescent galaxies and into distinct morphological types (using Sérsic index and bulge/disk decompositions). We observed larger sizes for early-type galaxies and smaller sizes for massive late-type galaxies in clusters in comparison to the field. We attribute this to longer quenching timescales of more massive galaxies in the cluster. Our analysis further revealed an increasing importance of recently quenched transition objects (“red disks”), where the correspondence between galaxy morphology and color is out of sync. This is a virialized population with sizes similar to the quiescent, spheroid-dominated population of the cluster center, but with disks still in-tact, and found at higher cluster-centric radii. The mass-size relation of cluster galaxies may therefore be understood as the consequence of a mix of progenitors formed at different quenching epochs. We also investigate the stellar-mass–size relation as a representation of galaxy sizes smoothly decreasing as a function of bulge fraction. We find that at an identical bulge-to-total ratio and identical stellar mass, quiescent galaxies are smaller than star forming galaxies. This is likely because of a fading of the outskirts of the disk, which we saw in comparing sizes of their disk-components. Ram-pressure stripping of the cold gas and other forms of more gradual gas starvation are likely responsible for this observation.